Pricing Credit Default Swap with Contagious Risk and Simulation - 郝瑞丽 张金清 刘永辉 胡周红 (Shanghai jiao tong da xue xue bao, 2016)
This paper mainly studies the pricing of credit default swap （CDS） with the loan as the reference asset, and gives a model based on the obtained conclusions. In the contract of CDS, we consider that the default of the protection＇s seller is correlated with the stochastic interest rate following Vasicek model and the default state of the reference firm. We give the pricing formula of CDS and analyze the effect of the contagious risk between the counterDarties on the Dricing of CDS.